Simultaneous and fast separation of three chlorogenic acids and two flavonoids from bamboo leaves extracts using zirconia. (September 2018) - Ma, Yilong; Zhu, Danye; Wang, Caihong; Zhang, Yingshuo; Shang, Yafang; Liu, Fengru; Ye, Tongqi; Chen, Xue; Wei, Zhaojun
Abstract: Phenolic acids and flavonoids in bamboo leaves are of great importance for their functional attributes, but they can hardly be separated simultaneously. In this study, zirconia was prepared and applied as a potential absorbent for simultaneous separation of these phenolic compounds. Three phenolic acids (neochlorogenic acid, chlorogenic acid and cryptochlorogenic acid) and two flavonoids (isoorientin and orientin) were isolated at the same time. The influence of bamboo leaves extraction conditions, zirconia calcination temperatures, desorption conditions and absorption/desorption dynamics on the separation were further investigated. When zirconia-400 (calcined at 400 °C) was treated with 70% ethanol extract of bamboo leaves for 40 min followed by desorption with 70% acetic acid solution for 60 min, the recovery of three chlorogenic acids and two flavonoids was about 65%. To conclude, the concise method developed here may provide a new way for simultaneous separation of phenolic acids and flavonoids from various plants. Graphical abstract: Highlights: The coexistence of neochlorogenic acid, chlorogenic acid and cryptochlorogenic acid was reported in bamboo leaves. Three chlorogenic acids and two flavonoids were simultaneously isolated from bamboo leaves extracts. Zirconia was proved to be a potential absorbent for simultaneous separation of phenolic acids and flavonoids.